An investigation into independent small business owners' perception of franchisee relationships. Issue 8 (10th August 2015) - Perrigot, Rozenn; Hussain, Dildar; Windsperger, Josef
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore independent small business owners' perceptions of franchisees relationships with their franchisors, their fellow franchisees within the chain, their employees and their customers. Design/methodology/approach – The authors use a qualitative approach and, more specifically, 26 in-depth interviews conducted with independent small business owners from various business sectors. Findings – These independent small business owners perceive that franchisees have a dependency-based relationship with their franchisors; a competition-based relationship with their fellow franchisees; a rather complicated relationship with their employees; and a superficial relationship with their customers. Research limitations/implications – This study contributes to the franchising literature by presenting an outside-chain view of franchisees' relationships with their franchisors, other franchisees, employees and customers. Practical implications – The findings may have practical implications for franchisors, enabling them to better understand the concerns of independent small business owners as potential franchisee candidates. Originality/value – The outside-chain view of franchisees' relationships is innovative.